2015
DOI: 10.3390/s150820392
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Foot Pathologies Based on Plantar Pressure Asymmetry

Abstract: Foot pathologies can negatively influence foot function, consequently impairing gait during daily activity, and severely impacting an individual’s quality of life. These pathologies are often painful and correspond with high or abnormal plantar pressure, which can result in asymmetry in the pressure distribution between the two feet. There is currently no general consensus on the presence of asymmetry in able-bodied gait, and plantar pressure analysis during gait is in dire need of a standardized method to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 46 publications
(69 reference statements)
6
64
0
2
Order By: Relevance
“…Evaluation of FFS was done by comparing the two potential points with the initiation of FSW at 1 st and 5 th Metatarsals. Wafai et al [17] presented a study of plantar pressure distribution during the whole stance phase and the outcome showed low-pressure distribution at the metatarsal region indicate the start of foot-flat for CS. Based on statistical results, Foot-Flat Start2 (FFS2) was found to be a suitable candidate as MD was 3.7 ms for CS and -18.5 ms for the intact side of TFA.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of FFS was done by comparing the two potential points with the initiation of FSW at 1 st and 5 th Metatarsals. Wafai et al [17] presented a study of plantar pressure distribution during the whole stance phase and the outcome showed low-pressure distribution at the metatarsal region indicate the start of foot-flat for CS. Based on statistical results, Foot-Flat Start2 (FFS2) was found to be a suitable candidate as MD was 3.7 ms for CS and -18.5 ms for the intact side of TFA.…”
Section: Resultsmentioning
confidence: 99%
“…This system model is based on measuring the plantar pressure between the foot of the individual and the outsole of the footwear, having an interface between the parts of an instrumented insole [17,86,87,88,89], as featured in Figure 7a.…”
Section: Applications Between Sports and Biomedical Areasmentioning
confidence: 99%
“…[17,86,87,88,89]. These plantar pressure concepts can be applied in high performance sports, not only in training or in the analysis of the assessments, but also, for example, in track sports, snowboarding and soccer [16,24,79].…”
Section: Applications Between Sports and Biomedical Areasmentioning
confidence: 99%
“…Foot plantar pressure measurement applications focus on measuring Figure 2a shows an illustration of a plantar pressure map during one stance phase (heel strike to heel off) of a healthy individual [27].…”
Section: Plantar Pressure Measurementmentioning
confidence: 99%
“…Figure 2a shows an illustration of a plantar pressure map during one stance phase (heel strike to heel off) of a healthy individual [27]. The foot and ankle provide the support and flexibility for weight bearing and weight shifting activities such as standing and walking.…”
Section: Plantar Pressure Measurementmentioning
confidence: 99%